ANALISIS KEPUASAN KERJA DAN DAMPAKNYA TERHADAP TURNOVER INTENTION DI PT ADIS DIMENSION FOOTWEAR - Farika, Virda; Nurdin, Mutmainnah (Universitas Ichsan Sidenreng Rappang, 2025)
The termination of employment asa a result of operational efficiency measures at PT Adis Dimension Footwear has created uncertainty and concern among active employees, particularly regarding increased workloads, inter-departemental rotations, and minimal overtime compensation.This study aims to analyze the level of job satisfaction among employees and its impact on turnover intention following the efficiency policy. A quantitative approach was used, employing a survey method with a five-point likert scale closed – ended questionnaire. A total of 30 respondents were selected using purposive sampling. The analysis results show that the average level of job statisfaction is relatively high (3,80), while turnover intention is at a moderate level (2,80). The simple linear regression results indicate a negative relationship with a weak influence (R2 = 2,1%). These findings suggest that although job satisfaction is relatively good, external factors such as work pressure and unclear work systems play a more dominant role in influencing the intention to resign. The implications of this study are expected to serve as a consideration for the company in formulating more humane and adaptive work policies.